HIV Prevalence Study and Costing Analysis undertaken for the development of an HIV/AIDS Workplace Strategy for Buffalo City Municipality - Thomas, EP; Colvin, M; Rosen, SB; Zuccarini, C; Petzer, S (Medical Research Council, 2005)
In contrast to most private sector employers in South Africa, local government has been slow to put in place HIV workplace strategies. While general workplace policies are available, there is an absence of specific guidelines for local authorities in their response as employers and as service delivery agencies to HIV/AIDS. The Buffalo City Municipality (BCM) embarked upon an innovative approach involving research and an inclusive process to develop a response to HIV/AIDS. This response is advocated as good practice. The report outlines the steps taken towards the development and adoption of a Buffalo City Municipality HIV strategy in late 2004. Lessons learned are documented for the benefit of other local authorities in the development of their own HIV strategies. The success in the development of the Buffalo City Municipality HIV/AIDS strategy is based on two important legs. Firstly, the process adopted and secondly the research initiative to provide the data to inform the HIV strategy. The process: BCM is to be commended for its innovative and proactive stance. Key to the success has been the leadership of the initiative where political councillors, departmental heads, and all levels of managers have supported the process. The outcome of the political support has been shown in the high rate of HIV testing in the sampled group, the enthusiastic take-up of Voluntary Counseling and Testing (VCT) by the employees, and the commitment to the resultant BCM HIV/AIDS Cross-cutting Strategy. Further, the involvement of staff from human resources and engineering through to finance and planning in the development of the BCM strategy again attests to the recognition that addressing HIV in the workforce and the broader community must be treated as an inter-sectoral and cross-cutting issue. The success of the process added considerably to the value and accomplishment of the research. The SA Medical Research Council (MRC) (an external group) was commissioned to undertake an HIV prevalence study, as they were seen to be independent and authoritive, as well as to carry out a Knowledge, Attitudes and Practice study (KAP) and to facilitate a VCT process. In addition, a health economist was requested to assess the cost implications of HIV for BCM as an employer. A team of external researchers worked closely with a BCM staff team in the design and setting up of the studies. The fieldwork took place in June 2004 and the overall BCM strategy was completed within two months, in August 2004. From a sample of 20% of the employees, the study found that 10.3% were HIV infected. Key findings are that temporary employees had a higher prevalence (7.7%) than permanent staff (9.3%). Women had a higher prevalence rate than men (10,2 and 9% respectively). The highest prevalence was in the 20-29 year age group. All job bands were infected but levels of infection were highest amongst the lower skill levels (11.7%) and black Africans (12.6%). There was no difference in infection level between employees with different educational levels.
Keywords: aids; africans; Baffalo City; workplace